(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: C-Peptide is a polypeptide hormone (31 amino acid residues) with molecular weight of 3.018 Dalton. It is a part of the pro-insulin molecule. Determination of C-peptide is useful in all cases in which the insulin assay would normally be used; antibodies and exogenous insulin therapy interfere with the insulin immunoassay. Aim: To determine the relation between the level of C-peptide in blood and saliva in children with Type 1 Diabetes Mellitus. Material & Method: Our study conducted in the Pediatric Diabetic Clinic of Al-Kadhimiya Teaching Hospital, Baghdad, Iraq, between March 2000 to April 2001. Fifty patients were involved in the study, blood aspiration and saliva samples were taken at morning from fasting known diabetic patients registered in diabetic clinic for measuring C-peptide level by using radio immunoassay kit (Cis, France), also serum glucose was measured. Results: The level of C- peptide in serum was about 6-7 times higher than saliva. Conclusion: The measurement of C-peptide in saliva is easy and reliable, with no disturbance or panic in pediatric age group. Keywords: C-peptide, Diabetes Mellitus, Saliva, Serum. Iraqi J Med Sci, 2004; Vol. 3 (1): 77-79